Hydrogen-bonding landscape of the carbamoylcyanonitrosomethanide anion in the crystal structure of its ammonium salt - Kostiantyn V. Domasevitch; Ganna A. Senchyk; Andrey B. Lysenko; Eduard B. Rusanov (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The structure of the title salt, ammonium carbamoylcyanonitrosomethanide, NH4+·C3H2N3O2−, features the co-existence of different hydrogen-bonding patterns, which are specific to each of the three functional groups (nitroso, carbamoyl and cyano) of the methanide anion. The nitroso O-atoms accept as many as three N—H...O bonds from the ammonium cations [N...O = 2.688 (3)–3.000 (3) Å] to form chains of fused rhombs [(NH4)(O)2]. The most prominent bonds of the carbamoyl groups are mutual and they yield 21 helices [N...O = 2.903 (2) Å], whereas the cyano N-atoms accept hydrogen bonds from sterically less accessible carbamoyl H-atoms [N...N = 3.004 (3) Å]. Two weaker NH4+...O=C bonds [N...O = 3.021 (2), 3.017 (2) Å] complete the hydrogen-bonded environment of the carbamoyl groups. A Hirshfeld surface analysis indicates that the most important interactions are overwhelmingly O...H/H...O and N...H/H...N, in total accounting for 64.1% of the contacts for the individual anions. The relatively simple scheme of these interactions allows the delineation of the supramolecular synthons, which may be applicable to crystal engineering of hydrogen-bonded solids containing polyfunctional methanide anions.